Nitrogen-containing compounds from pseuderanthemum carruthersii var. Atropurpureum - Vo , Thi Nga; Hoang , Minh Hao; Nguyen , Kim Phi Phung (Journal of Technical Education Science, 2018)
Genus Pseuderanthemum (Acanthaceae) has 10 species in Vietnam. Pseuderanthemum genus is attracting the attention of many research groups in pharmacology and chemistry. One of these species is Pseuderanthemum carruthersii (Seem.) Guill. var. atropurpureum (Bull.) Fosb. used in traditional remedies to heal the wounds due to its anti–inflammatory activity. Using column chromatographic method with absorbents including silica gel and sephadex LH20, four nitrogen-containing compounds were isolated from the dried leaves of Pseuderanthemum carruthersii (Seem.) Guill. var. atropurpureum (Bull.) Fosb. (Acanthaceae). They included indole 3–carboxaldehyde (1), uracil (2), adenine (3), and betaine (4). The chemical structures of these compound were elucidated by using spectroscopic analysis (nuclear magnetic resonance spectroscopy, mass spectrometry and infrared spectroscopy) and reflecting with reported data in the literature. To the best of our knowledge, the former three mentioned substances, indole 3–carboxaldehyde (1), uracil (2) and adenine (3), were isolated for the first time from this genus.